A bruxaria como mecanismo de repressão feminina : uma análise do Malleus Maleficarum (1486) a partir do inquérito das testemunhas - Silvino, Deisiane dos Santos (2024)
This present work makes a critical analysis of the third part of the work Malleus Maleficarum. The aim is to understand the processes that triggered the hunt for Witches in Europe, at the end of the Middle Ages and the beginning of the Modern Age. The focus of this research is the Witch woman and the witness of the investigations. The production of this manual began in 1484, through authorization from the Pope to Innocent VIII (1484-1492). The authors of this treatise are two Dominican priests Heinrich Kramer and James Sprenger, the main writer is Kramer. This book became the main model in Europe for trials involving accusations of witchcraft. Therefore, the main objective of this research is to understand the motivations that led to choosing the woman as a “scapegoat”, understanding who these women were and meeting the witnesses. So, first, we contextualized the widespread hatred of women and identified who these women were. It was found that the majority of women accused of witchcraft practiced traditional medicine, that is, they were midwives and healers. At a time when medicine was on the rise, these healers were seen as threats to faith and the structure of society. Furthermore, we found that, for the most part, the witnesses were neighbors who had some disagreement with the accused.